Kompatibilitas Adat Perkawinan Jawa Banten terhadap Hukum Islam dan Uu No 16 Tahun 2019 Jo. UU No 1 Tahun 1974 tentang Perkawinan - Muhamad Wahyudin; Muhammad Ishom; B. Syafuri (Qonuni: Jurnal Hukum dan Pengkajian Islam, 2024)
Javanese marriage customs in Banten reflect philosophical, social, and religious values that play a vital role in shaping ideal families and fostering social cohesion. However, modernization and globalization threaten the continuity of these traditions, especially among younger generations who often perceive them as outdated. This study employs a qualitative approach with normative juridical methods, supported by field data collected through observations and interviews with traditional leaders, religious scholars, married couples, and academics in the Banten region. The findings reveal that Javanese marriage traditions embody values such as mutual cooperation, empathy, and respect for parents—principles that align with Islamic teachings. Nonetheless, certain symbolic practices that are burdensome or potentially incompatible with Islamic law require contextual reconstruction. The Islamic legal concept of ‘urf (custom) provides legitimacy for traditions that do not contradict sharia and offers a framework for harmonizing local culture with Islamic principles. Through adaptive reconstruction, essential cultural values can be preserved while meeting the needs of modern society. This study recommends cultural education, simplification of rituals, and supportive policy frameworks as sustainable strategies for cultural preservation.